Enterprise-led internet healthcare provision in China: insights from a leading platform - Wang, Li; Liang, Dan; HuangFu, Hengqian; Ke, Changwen; Wu, Shaolong; Lai, Yingsi (Frontiers in Digital Health, 2025)
BackgroundChina's healthcare resources are limited and unevenly distributed, with a notable urban-rural gap. Enterprise-led internet healthcare platforms have become an important solution for optimizing resource allocation, improving accessibility, and enhancing efficiency in mainland China. However, detailed analysis of their online consultation services from both healthcare provider and patient perspectives is still lacking.ObjectiveThe online consultation data of an enterprise-led internet healthcare platform was depicted and analyzed to understand the temporal trend and current situation of enterprise-led internet healthcare development in mainland China, which provided insights for the further development of internet healthcare.MethodsWe gathered information from an enterprise-led internet healthcare platform (i.e., Good Doctor Online) covering the period from January 2008 to December 2022, including the characteristics of doctors, healthcare institutions, and patients. Based on the above data, we sketched and analyzed the situation of online consultation services provided by the enterprise-led internet healthcare platform in mainland China.ResultsA total of 149,890 doctors from 7,584 healthcare institutions provided 40,462,801 online consultations from January 2008 to December 2022. Doctors and healthcare institutions providing online consultation services were primarily distributed in the economically developed eastern and southern provinces of China. Doctors with intermediate (30.15%) and senior titles (58.12%) were the main providers of online consultations and most doctors were from tertiary hospitals (88.18%). The consultation price median [interquartile range (IQR)] was 49.00 (15.00, 100.00) RMB. The health issues with the highest consultation frequency included upper respiratory tract infections or fever (16.19%), gynecological disorders (11.98%), and skin diseases (8.65%), with variations in gender and age. The age distribution of patients showed two peaks in age groups <5 years and 20–39 years, with the median age (IQR) 29.00 (19.00–43.00) years.ConclusionsEnterprise-led internet healthcare platforms enhance access to care and reduce offline resource strain, especially during COVID-19. They mainly address non-urgent conditions but cannot fully replace in-person care. Policies should focus on increasing elderly participation, engaging senior doctors, optimizing male-oriented services, expanding access to underserved areas, standardizing pricing, and broadening insurance reimbursement coverage to improve equity and sustainability.